GENOTYPE OF Cryptosporidium spp. ISOLATED FROM BOVINE OF AL-QADISIYAH PROVINCE /IRAQ - ِِAsmaa Al-Jawasim (Basrah Journal of Veterinary Research)
The current research included examination of 100 fecal sample from bovine wascollected from AL-Qadisiyah province, from September 2018 until February 2019.TheMicroscopically result showed that oval or spherical shaped with dark pink color or redoocyst on blue ground and 30(30%) positive sample out 100 case . It was recorded thatthe maximum rate 41.66% (5/12) was seen in November, but the lowest rate 18.75%(3/16) was seen in the month of February with no significant differences at level(p<0.05.) According to age the maximum rate of incidence 40%(14/35)was found inthe age group lower than a month, but the lowest incidence was seen in the group( >1years). There is no significant differences at p<0.05.between male and female. In thecurrently study the N-PCR in molecular investigation were used ,the positive samplewas18 (60%) out of 30 fecal sample. Sequencing of a fragment of the(18s rRNA) gene(834 bp) that separated from many distinct area in AL- Qadisiyah governmentrecorded (50%)6/12 sample related to NCBI – Blast Cryptosporidium parvum ,( 33.33%)4/12 sample display deep related to NCBI –Blast Cryptosporidium bovis (this firststudy reported C. bovis in Iraq ) , (16.66%) 2/12 sample showed closed related to NCBI–Blast Cryptosporidiumandersoni.